A systematic review investigating advances in gene therapy for Fanconi anemia over the last three decades - McLeman, Lorna M.; Glaser, Astrid; Conyers, Rachel; Deans, Andrew J. (Frontiers in Hematology, 2023)
Fanconi anemia (FA) is the most common inherited bone marrow failure syndrome, characterized by cellular DNA repair deficiency, developmental defects, and a 700-fold increased risk of developing cancer. Bone marrow transplant is the only treatment option for the haematological manifestations of FA, but it can have serious complications. Gene therapy, on the other hand, offers a promising alternative by using the patient's own cells that have been corrected ex vivo. However, due to the complexity of cells with a compromised DNA repair pathway, it has been difficult to achieve success in treating FA with gene therapy, despite advancements in treatment of other blood disorders. This review summarizes all the published human trials to date, including a recent study that reported success in treating 4 pediatric patients with gene therapy, and it's interim Phase 2 study that has successfully treated 6 further. We discuss the key advances such as improvements in viral vectors, shorter ex vivo transduction protocols and use of hypoxia and/or media additives such as Nacetylcysteine or etanercept. We also discuss the potential use of mobilizing agents, such as GCSF and plerixafor. The data from human trials are systematically reviewed and advances in murine and in vitro studies are discussed.